A Vision of Reading. Issue 3 (March 2016) - Grainger, Jonathan; Dufau, Stéphane; Ziegler, Johannes C.
Abstract : Different fields of research within the cognitive sciences have investigated basic processes in reading, but progress has been hampered by limited cross-fertilization. We propose a theoretical framework aimed at facilitating integration of findings obtained via these different approaches with respect to the impact of visual factors on reading. We describe a specialized system for parallel letter processing that assigns letter identities to different locations along the horizontal meridian within the limits imposed by visual acuity and crowding. Spatial attention is used to set up this system during reading development, and difficulty in doing so has repercussions in terms of efficient translation of the orthographic code into its phonological counterpart, and fast access to semantics from print. Trends: Processing of orthographic information begins with scale-invariant gaze-centered letter detectors that conjunctively encode letter identity and letter location. Visual acuity, crowding, and spatial attention conjointly determine activity in these gaze-centered letter detectors. Location-invariant orthographic processing involves the computation of orthographic chunks and orthographic features. Orthographic chunks encode highly co-occurring letter combinations using precise information about letter order. Orthographic features encode diagnostic information with respect to word identity using more flexible letter position information. Orthographic processing operates in parallel across multiple words and is pooled into a single processing channel, hence allowing orthographic overlap across neighboring words in a sentence to exert a mutually facilitatory influence.